CURRENT TRENDS OF ICT SECTOR DEVELOPMENT IN UKRAINE - PROTSYKEVYCH, Arsen; PROTSYKEVYCH, Ksenia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article emphasizes the priority role of the ICT sector in building a highly developed and competitive national economy. Attention was drawn to the ability of the ICT sector to improve the country’s adaptation to globalization and neo-industrial challenges. The role of the ICT sector in the course of our country overcoming hybrid risks and threats and challenges of a full-scale military invasion and subsequent post-war recovery is increasing. An economic and statistical analysis of the number of enterprises (business entities) by type of economic activity «Information and telecommunications» in Ukraine in 2010-2022 was carried out and their absolute growth, growth rate, absolute value of 1% of growth, average annual value, average annual absolute growth and growth rate. It was established that during the analyzed period, the number of subjects of this type of economic activity increased by 5.3 times, while the annual increase was 20 units or 14.9%. If in 2010 there were 55.9 thousand business entities in the field of information and telecommunications, then in 2022 their number was 295.9 thousand units. The shares of enterprises (business entities) by the type of economic activity «Information and telecommunications» in the total number of enterprises (business entities) in Ukraine in 2010-2022 were calculated. It was concluded that the share of entities of this type of economic activity in the total the number of enterprises in Ukraine is constantly increasing and in 2022 was equal to 4.5%, which is by 1% more compared to 2010. It was emphasized that in order to increase the intensity of the development of the ICT sector, it is necessary to change the state’s approach to ensuring the digitalization of the economy and the development of the information society, while providing support, guarantees, broad opportunities for businesses to realize their own economic interests.